Adaptation and validation to the spanish context of the scale of self-stigma in relatives of people with mental illness - Trigueros, Rubén; Aguilar-Parra, José Manuel; Cangas, Adolfo Javier; Ortiz, Luis; Navarro, Noelia (Anales de Psicología / Annals of Psychology, 2019)
Stigma, and in particular self-stigma in people with severe mental disorder (GIST), is one of the main problems faced by mental health professionals. However, this problem is not only found in people who suffer from this mental illness, but its consequences affect family members in the same way. For this reason, it is necessary to adapt and validate in the Spanish context the Scale of Self-Stigma in Relatives of People with Mental Illness (AFPEM). The study involved 304 adults (M = 44.57, SD = 15.29). To analyze the psychometric properties of the scale, several analyzes have been carried out. The results of the confirmatory factorial analysis (CFA) have offered support to the questionnaire structure of 30 items, 10 items and the higher order model. The structure of the models was invariant respect to gender. Cronbach's alpha values ​​were greater than .70 in the different subscales. The results of this study have provided evidence of validity and reliability of the AFPEM, so that various mental health professionals will have an instrument with which assesses the degree of self-stigma that family members of people with SMI have.